APPLICATION OF JIGSAW MODELS ON CARBON COMPOUND DERIVATIVES OF ALKANES MATERIALS TO FURTHER SCHOOLER ACTIVITIES - Mariani Surtiningsih (PPG IKIP Siliwangi, 2023)
This research is motivated by the fact that there are low achievement levels and a need for more active student participation in the learning activities of. An action research study was conducted to improve student learning outcomes using the Jigsaw Method to address this issue. The stages in the cooperative learning Jigsaw method consist of forming original groups, assigning problems to each student, preparing students within expert teams, and returning students to their original groups. The classroom action research used in this study follows the Kemmis and Mc. The Taggart method is a self-spiraling system consisting of four stages: planning, action, observation, reflection, and re-planning. Data from the research were obtained from 1) Observation of student activity and teacher performance, 2) Formative tests at the end of each action, and 3) Student response scale questionnaires regarding Jigsaw cooperative learning. The data analysis technique used was simple qualitative descriptive statistics. The research results indicate the following: 1) Student activity index increased by 18.67% from cycle I to cycle II, 2) Improvement in student learning outcomes from pre-PTK to cycle I was 15.84%, and from cycle I to cycle II it was 9.16%, 3) Student response to learning reached a score of 77.93%, indicating that students responded positively to the learning.